2021
DOI: 10.1007/s00704-021-03725-7
|View full text |Cite
|
Sign up to set email alerts
|

Rice yield responses in Bangladesh to large-scale atmospheric oscillation using multifactorial model

Abstract: This paper intends to explore rice yield fluctuations to large-scale atmospheric circulation indices (LACIs) in Bangladesh. The annual dataset of climate-derived yield index (CDYI), estimated using principal component analysis of Aus rice yield data of 23 districts, and five LACIs for the period 1980-2017 were used for this purpose. The key outcomes of the study were as follows: (1) three sub-regions of Bangladesh, northern, northwestern, and northeastern, showed different kinds of CDYI anomalies; (2) the CDYI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The reason for meteorological hotspots is that these regions are surrounded by the foothills of the Himalayan Mountain, making it hard for the southwest monsoon to release its moisture after the air in this region sinks, triggering this region to become a meteorological hotspot with recurrent drought events. This outcome is consistent with earlier works 64 , 68 , 69 . For example, Hossain et al and Shahid et al 11 , 70 showed that the frequency and intensity of moderate drought events have increased in the northwest region.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The reason for meteorological hotspots is that these regions are surrounded by the foothills of the Himalayan Mountain, making it hard for the southwest monsoon to release its moisture after the air in this region sinks, triggering this region to become a meteorological hotspot with recurrent drought events. This outcome is consistent with earlier works 64 , 68 , 69 . For example, Hossain et al and Shahid et al 11 , 70 showed that the frequency and intensity of moderate drought events have increased in the northwest region.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the country's monsoon rainfall pattern is influenced by an irregular atmospheric circulation pattern known as the Southern Oscillation (SO), which reflects a relationship with EL Nino, or the quasi-periodic warming of sea surface temperature (SST) 50 in a phenomenon known collectively as El Nino-Southern Oscillation (ENSO). Low rainfall occurred during the years of moderate El Nino (2002–2003 and 2009–2010) and strong El Nino (2014–2016) 63 , 64 . The long-term dry phase increases as SST are closely associated with the rainfall pattern 58 , 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate how climate affects rice production at various sites and locations. Seasonality and regional climatic variability have an impact on rice crop productivity [ 20 , 21 ]. According to [ 9 , 28 ], the research area’s harsh weather conditions, including drought and flooding, make Aman yield the most sensitive to climate change among the three rice crop ecotypes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies can aid in meeting policymakers’ evidence requirements at the regional level and for various socioeconomic groups. There is a shortage of quantitative rice yield datasets on climate change effects, principally at regional and national levels [ 20 ]. This gap occurs in the dataset concerning Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Located in a tropical monsoonal climatic region, Bangladesh receives nearly 2200 mm of rainfall every year, which supports agriculture, the environment and livelihood activities since time immemorial [1][2][3] . However, the country is susceptible to hydrometeorological hazards due to its flat topography and high rainfall seasonality 4,5 .…”
Section: Introductionmentioning
confidence: 99%